Does migration 'pay off' for foreign-born migrant health workers? An exploratory analysis using the global WageIndicator dataset. Issue 1 (December 2016) - de Vries, Daniel; Steinmetz, Stephanie; Tijdens, Kea
Abstract Background This study used the global WageIndicator web survey to answer the following research questions: (RQ1) What are the migration patterns of health workers? (RQ2) What are the personal and occupational drivers of migration? (RQ3) Are foreign-born migrant health workers discriminated against in their destination countries? Methods Of the unweighted data collected in 2006–2014 from health workers aged 15–64 in paid employment, 7.9 % were on migrants (N  = 44, 394; 36 countries). To answer RQ1, binary logistic regression models were applied to the full sample. To answer RQ2, binary logistic regression was used to compare data on migrants with that on native respondents from the same source countries, a condition met by only four African countries (N  = 890) and five Latin American countries (N  = 6356). To answer RQ3, a multilevel analysis was applied to the full sample to take into account the nested structure of the data (N  = 33, 765 individual observations nested within 31 countries). Results RQ1: 57 % migrated to a country where the same language is spoken, 33 % migrated to neighbouring countries and 21 % migrated to former colonizing countries. Women and nurses migrated to neighbouring countries, nurses and older and highly educated workers to former colonizing countries and highly educated health workers and medical doctors to countries that have a language match. RQ2: In the African countries, nurses more often out-migrated compared to other health workers; in the Latin American countries, this is the case for doctors. Out-migrated health workers earn more and work fewer hours than comparable workers in source countries, but only Latin American health workers reported a higher level of life satisfaction. RQ3: We did not detect discrimination against migrants with respect to wages and occupational status. However, there seems to be a small wage premium for the group of migrants in other healthcare occupations. Except doctors, migrant health workers reported a lower level of life satisfaction. Conclusions Migration generally seems to 'pay off' in terms of work and labour conditions, although accrued benefits are not equal for all cadres, regions and routes. Because theWageIndicator survey is a voluntary survey, these findings are exploratory rather than representative.